VD_FINDINFO Jug / 2017 / 67 vom 12. September 2016 - VD Tribunal cantonal (2016)
DROIT D'ÊTRE ENTENDU, MOTIVATION DE LA DÉCISION, ADMISSION DE LA DEMANDE | 29 al. 2 Cst., 3 al. 2 let. c CPP (CH), 409 CPP (CH)